Limits to disclosures and the continuum of labour exploitation in the Bangladeshi ready-made garment sector. Issue 2 (17th February 2023) - Ahmed, Shaila; Arun, Shoba
ABSTRACT: This paper questions if enough is done to tackle modern slavery within the ready-made garments (RMG) supply chains, through the lens of disclosures in improving work practices. Using evidence from Bangladesh, we find how there is a continuum of labour exploitation where the reality of forced labour is not a static one, but a continuum of experiences highlighting the complexity of the exploitative environment within the dominant neoliberal logic of transparency disclosures. It is imperative not only to make disclosures more robust through due diligence, but support capacity to address exploitation at the lower end of the supply chain.